Myocardial Damage in a Highly Suspected Case With Paraneoplastic Pemphigus: A Case Report and Literature Review - Du, Xiao; Zhang, Miao; Zhang, Shilan; Tian, Feng; Wen, Tie; Liu, Ling (Frontiers in Medicine, 2022)
paraneoplastic pemphigus (PNP) is a rare mucocutaneous autoimmune disease. It has multiple clinical accompanied symptoms via affecting various types of epithelia, including gastrointestinal and respiratory tract. However, extensive review of the literature found no cases of paraneoplastic pemphigus (PNP) associated with myocardial damage. Here, we present a 56-year-old male patient with clinically and histopathologically typical paraneoplastic pemphigus (PNP), who showed persistent myocardial damage for non-cardiac disease involvement. Therefore, we believe that in patients with paraneoplastic pemphigus (PNP), the possibility of combined myocardial damage should be considered when persistent myocardial enzyme markers are elevated in order to diagnose and treat patients promptly.